PERAMALAN HARGA BERAS PREMIUM BULANAN DI TINGKAT PENGGILINGAN MENGGUNAKAN FUZZY TIME SERIES MARKOV CHAIN - Sari, Virgania; Hariyanto, Sylvia Ayu (Jurnal Gaussian, 2023)
Rice is one of the crucial food commodities in Indonesia whose price fluctuates every year. Forecasting is the science of predicting an event in the future and predicting future conditions using historical data. One of the forecasting methods is the Fuzzy Time Series which is used to predict time series data that can be widely used on any real time data. This research used forecasting with the Fuzzy Time Series Markov Chain method because this method provides a good accuracy value. The historical data used is monthly data on the average price of premium rice at the Indonesian mill level for the period January 2014-July 2022 then divided into training data and testing data. The error rate used is MAPE and the results of calculations with Fuzzy Time Series Markov Chain on data testing the period November 2020-July 2022 obtained a very good MAPE value of 0.81%. Forecasting results for the period August 2022 obtained the results of Rp. 9.627,99